Freedom from a humanistic and existencial perspective - Salomón Paredes, Alejandro Khaled (2013)
This article discusses the possibility of human freedom in relation to its existential counterpart: states the limits where the person limits (neurosis, mental disorders, “somatógenas” conditions) with an integrated look, spacious and cozy regarding restriction states of freedom as possible, necessary and fully human. Regarding authors such as N. Hartmann, V. Frankl, F. Perls, S. Kierkegaard, M. Scheler, K. Jaspers, E. Martinez, K. Dabrowski, among others, in relation to the concepts of freedom and states of restriction of freedom and responsibility. Starting from this integrated vision of existence, it pretends to open up possibilities for work-oriented psychotherapeutic acceptance of what exists in the here and now, both the emotional as the experience and situation, for a fully human existence as possible.